Population Pharmacokinetic Model Characterizing 24‐Hour Variation in the Pharmacokinetics of Oral and Intravenous Midazolam in Healthy Volunteers. (24th July 2015) - van Rongen, A; Kervezee, L; Brill, MJE; van Meir, H; den Hartigh, J; Guchelaar, H‐J; Meijer, JH; Burggraaf, J; van Oosterhout, F
<x xml:space="preserve">Abstract</x> Daily rhythms in physiology may affect the pharmacokinetics of a drug. The aim of this study was to evaluate 24‐hour variation in the pharmacokinetics of the CYP3A substrate midazolam. Oral (2 mg) and intravenous (1 mg) midazolam was administered at six timepoints throughout the 24‐hour period in 12 healthy volunteers. Oral bioavailability (population mean value [RSE%] of 0.28 (7.1%)) showed 24‐hour variation that was best parameterized as a cosine function with an amplitude of 0.04 (17.3%) and a peak at 12:14 in the afternoon. The absorption rate constant was 1.41 (4.7%) times increased after drug administration at 14:00. Clearance (0.38 L/min (4.8%)) showed a minor 24‐hour variation with an amplitude of 0.03 (14.8%) L/min and a peak at 18:50. Simulations show that dosing time minimally affects the concentration time profiles after intravenous administration, while concentrations are higher during the day compared to the night after oral dosing, reflecting considerable variation in intestinal processes.